1990
DOI: 10.1037/h0079194
|View full text |Cite
|
Sign up to set email alerts
|

Men as elder caregivers: A response to changing families.

Abstract: Results are presented from a study that examined the relationship between gender orientation and the unique stresses and gratifications for men who are engaged in caregiving tasks traditionally performed by women. The men report having found emotional gratification an important motivating factor, and they tended to ascribe to themselves many affective traits usually associated with the female role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
9

Year Published

1991
1991
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 25 publications
0
13
0
9
Order By: Relevance
“…A good deal of research, under the broad rubric of standpoint theory (Collins, 1986;Harding, 1991), has shown that both women and men can develop abilities and inclinations not conventionally associated with their gender roles. For instance, two studies showed that men who were primary caregivers for children or parents were as nurturing, attentive to others, and emotionally supportive as most women and more so than most men (Risman, 1989;Kaye & Applegate, 1990). Conversely, Epstein's (1981) in-depth study showed that women in law became as confident, ambitious, assertive, and competitive as many men and more so than other women in general.…”
Section: The Missing Critical Edge In Gray' S Workmentioning
confidence: 90%
“…A good deal of research, under the broad rubric of standpoint theory (Collins, 1986;Harding, 1991), has shown that both women and men can develop abilities and inclinations not conventionally associated with their gender roles. For instance, two studies showed that men who were primary caregivers for children or parents were as nurturing, attentive to others, and emotionally supportive as most women and more so than most men (Risman, 1989;Kaye & Applegate, 1990). Conversely, Epstein's (1981) in-depth study showed that women in law became as confident, ambitious, assertive, and competitive as many men and more so than other women in general.…”
Section: The Missing Critical Edge In Gray' S Workmentioning
confidence: 90%
“…Rossi and Rossi (1990) found that part but not all of the gender‐related difference in parent‐child closeness was related to differences in gender‐linked personality characteristics they called expressivity and dominance. These characteristics reflect the expressive‐instrumental dichotomy many behavioral scientists associate with traditional Western gender role socialization (e.g., Kaye & Applegate, 1990). Parents who rated themselves higher in expressivity reported greater affective closeness with their adult children than less expressive parents.…”
Section: Intergenerational Researchmentioning
confidence: 99%
“…However, since males already constitute more than one-third of caregivers, the impact of caregiving on their well-being cannot be ignored (Stone et al, 1987). It is expected that the number of male caregivers will continue to increase in the future, and that a larger percentage of the caregiver responsibilities will be placed on males since a greater number of women than men are diagnosed with dementia (Fitting et al, 1986;Kaye and Applegate, 1990). Understanding the impact of the caregiving situation on male caregivers regarding psychiatric morbidity will help to determine if changes in support services will need to be addressed in the present and the future.…”
Section: Introductionmentioning
confidence: 98%